2022
DOI: 10.1136/bmjopen-2021-056875
|View full text |Cite
|
Sign up to set email alerts
|

Guidance relevant to the reporting of health equity in observational research: a scoping review protocol

Abstract: IntroductionHealth inequities are defined as unfair and avoidable differences in health between groups within a population. Most health research is conducted through observational studies, which are able to offer real-world insights about etiology, healthcare policy/programme effectiveness and the impacts of socioeconomic factors. However, most published reports of observational studies do not address how their findings relate to health equity. Our team seeks to develop equity-relevant reporting guidance as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Reporting guidelines specific to mental health screening tools would help researchers conducting future validation studies to report on the information needed for appraisal and synthesis. Ongoing initiatives to develop an equity extension of the widely used Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline may help in this regard ( Rizvi et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reporting guidelines specific to mental health screening tools would help researchers conducting future validation studies to report on the information needed for appraisal and synthesis. Ongoing initiatives to develop an equity extension of the widely used Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline may help in this regard ( Rizvi et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We will review the candidate items supported from scoping review and the items found to be poorly reported in the methods study. Study design details regarding the methods studies will be published on open access platforms or published in peer review journals when possible [ 64 – 66 ]. We will analyze focus groups thematically and use themes to generate additional candidate items.…”
Section: Methodsmentioning
confidence: 99%
“…The search terms will be based on previous works to reflect three concepts: (1) inequality, (2) health service coverage and (3) African regions (online supplemental appendix 3). For inequality, we will adapt a validated search filter,25 by including adding other terms that are suitable for the African context (eg, rural and religion) 26–28. For service coverage, we will use terms related to UHC that were previously identified with an exploratory search in Google, Google Scholar and Abstract reviews 29.…”
Section: Methods and Analysismentioning
confidence: 99%
“…For inequality, we will adapt a validated search filter, 25 by including adding other terms that are suitable for the African context (eg, rural and religion). [26][27][28] For service coverage, we will use terms related to UHC that were previously identified with an exploratory search in Google, Google Scholar and Abstract reviews. 29 For African geographic regions, we will adapt a geographic African filter validated by the South African Cochrane Centre, 30 by correcting the name 'Mayotte' and including alternative missing African country names (eg, 'Ruanda', 'Comoros' and 'Cabo Verde').…”
Section: Literature Searchmentioning
confidence: 99%